Evaluando la usabilidad en aplicaciones para la TVDi - Febles Estrada, Ailyn (2012)
The evolution of Television as a source of information has reached the top of quality whith the Interactive Digital Television (TVDi), a technological step that allow users to become active from pasive. TVDi program is, on informatic terms, a software that give the TV viewer some specific capabilities. The recent emergence of that kind of application with all that functional and not functional specs and features; reveals an amount of new problems poorly or absolutely not approached in that knowledge area. That is, as an example, the methodologies for the developement of this applications, the quality attributes to fulfill and the techniques for proving them and so on. One of the most remarcable problems is that of the software product designs which do not fulfill some elemental requirements that ensure the app to be used in the correct manner. It has been associated with the quality attribute known as Usability. This article adresses some of the good prctice to have in mind when evaluating usability in the apps developed for TVDi.